Pre Sterilization Effect towards the Successful of the Initiation of Sengon Explant Shoots - Y.M.M Anita Nugraheni; Ratna Uli Damayanti Sianturi; Yulianti Bramasto (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
Sengon known as forest product with high market demand. Tissue culture is one multiplication method to get seeds in large quantities. One factors that support the success of reproduction is the health of the plant material. The purpose of the study is to determine the influence of pre-sterilization treatments towards the successful initiation of sengon organogenesis. The research method was done by spraying the seedlings with Pyraclostrobin 50 g.kg -1+ Metiram 550 g.kg -1of 2,500 ppm every week for 3 months. Each explant was grown on MS medium.The observation was carried out done every 1 week for 12 weeks, including the amount of contamination (bacteria, fungi), browning and the appearance of buds, roots and callus. Data were analyzed by t-test. The next stage is multiplication by using treatments of 24D 0.1 mM, 24D 0.5 mM, BAP 0.5 mM, BAP 2 mM, K 0.1 mM, K 0.5 mM, TDZ 0.1 mM, TDZ 0, 5 mM, and control. Completely randomized design was used and analyzed by using one way ANOVA, and tested with Duncan for the differences at 0,05 significant level. The results showed that pra-sterilization treatment was capable of supporting the successful initiation of sengon shoots characterized by low levels of contamination, increased number of callus and number of sengon shoots explants. Kinetin 0.01 mM in the multiplication media of sengon shoots was able to increase the number of adventitious shoots.